Common variants in the CPT1A gene are associated with cataracts in Northern breeds of domestic dog - Sally L. Ricketts; Saija Ahonen; Louise Pettitt; Jamie Freyer; Stuart Ellis; Christopher A. Jenkins; Maria Kaukonen; Mike Boursnell; Ellen Schofield; Oliver P. Forman; Hannes Lohi; Cathryn S. Mellersh (PLoS ONE, 2025)
Primary hereditary cataract affects many purebred domestic dog breeds and is a major cause of visual impairment in dogs. Cataracts are common in Northern breeds such as the Siberian Husky, Alaskan Malamute and Samoyed, but their aetiology is currently unknown. Only two genetic loci are known to be causally related to primary hereditary cataracts in the dog. To search for genetic loci associated with cataracts in Northern breeds, we used a genome-wide association study approach in three breeds—Siberian Husky, Alaskan Malamute and Samoyed. Cases were defined as dogs with bilateral posterior polar subcapsular cataracts and controls were at least four years of age with no evidence of cataracts or other ocular abnormality. We found a genome-wide statistical association for cataracts in the Siberian Husky on canine chromosome 18 (P-value: 1.1 x 10 − 7), which was independently replicated in a second larger case-control set (P-value 9.8 x 10 − 29). The Samoyed breed also showed evidence for association in the same genomic region (P-value: 2.4 x 10 − 5). We subsequently used targeted resequencing of the associated region (6.5 Mb) in ten Siberian Huskies and whole genome sequencing of a Husky, Malamute, Samoyed and Norwegian Buhund case to conduct fine-mapping and screen for candidate causal variants. These analyses identified a region of linkage disequilibrium in the four breeds containing common variants in the carnitine palmitoyltransferase 1A (CPT1A) gene that are strongly associated with bilateral posterior polar subcapsular cataracts in the Siberian Husky, Samoyed, Icelandic Sheepdog and Norwegian Buhund and we demonstrate that CPT1A is expressed in the dog lens and retina through RNAseq. Our findings represent a novel locus for cataracts in dogs. However, further work is needed to elucidate the pathophysiology underlying the association between CPT1A and cataracts in Northern breeds.